The motives of strategic alliances among construction companies in Johor Bahru / Marlina Ismail - Ismail, Marlina (Faculty of Business and Management, 2011)
Strategic alliances are a vital and popular alternative for survival and growth of the company in order to face with the intense and global competition. Nowadays, strategic alliances are becoming an increasingly important in construction industry. Malaysia began develop its construction industry since independence and this industry plays an important role in generating wealth as well as improving the quality life of Malaysian. The purpose of this research is to determine and understand why construction companies in Johor Bahru are opting for strategic alliances. The research aims in assisting construction companies in order to be a major industry in the country.